The new reality: participation of elected government officials of the state of Kansas in emergency management training post September 11, 2001 - Norton, Susan Parkinson (Kansas State University, 2007)
This study sought to understand reasons for participation and non-participation in national incident management system (NIMS) and incident command system (ICS) training by elected officials in the state of Kansas as well as motivations and perceived barriers to participation in this training. County commissioners and mayors from first class and second class cities in the state were the population for this study (n = 202). One instrument comprised of three parts was utilized; a slightly modified version of the Deterrents to Participation Scale (DPS-G) developed by Darkenwald and Valentine in 1984, a slightly modified version of the Education Participation Scale (EPS-A) used by Morstain and Smart (1974) and based on the original work of Boshier (1971), and the third part of the instrument which gathered demographic information. Findings for the study noted that while there was a self-reported percentage of over 51% completion of NIMS training, the target population may be unaware of the Homeland Security and Kansas Emergency Management parameter for participation and are not in compliance with the emergency management institute (EMI) testing and reporting standards. The question of motivations to participation noted that although the EPS-A showed strong reliability to the target population, upon closer scrutiny the questions did not align for this population as they had for previously surveyed populations. A new version of the EPS for elected officials has been suggested for subsequent studies. The DPS-G was found to be a valid and reliable instrument for the target population. Additional demographic variables of age, rural/urban and time in position were explored. None of these variables were found to be significant to the participation decision. The possibility of a prediction model for participation was explored through a stepwise logistic regression. The model should be explored further utilizing several factors from the DPS – G (personal problems, lack of personal priority, and lack of confidence) as possible significant barriers. The qualitative responses on the survey noted the high percentage of respondents that had a lack of knowledge or understanding of the requirements or had questions on availability of the training. Implications and recommendations for the target populations and to the field of study are discussed.
Keywords: Adult Education; Elected officials; Kansas; Mayors; County Commissioners; Participation; Education, Adult and Continuing (0516)